Selection of antimicrobial frog peptides and temporin‐1DRa analogues for treatment of bacterial infections based on their cytotoxicity and differential activity against pathogens. (19th September 2020) - Gaiser, Rogier A.; Ayerra Mangado, Jaione; Mechkarska, Milena; Kaman, Wendy E.; van Baarlen, Peter; Conlon, J. Michael; Wells, Jerry M.
Abstract: Cationic, amphipathic, α‐helical host‐defense peptides (HDPs) that are naturally secreted by certain species of frogs (Anura) possess potent broad‐spectrum antimicrobial activity and show therapeutic potential as alternatives to treat infections by multidrug‐resistant pathogens. Fourteen amphibian skin peptides and twelve analogues of temporin‐1DRa were studied for their antimicrobial activities against clinically relevant human or animal skin infection‐associated pathogens. For comparison, antimicrobial potencies of frog skin peptides against a range of probiotic lactobacilli were determined. We used the VITEK 2 system to define a profile of antibiotic susceptibility for the bacterial panel. The minimal inhibitory concentration (MIC) values of the naturally occurring temporin‐1DRa, CPF‐AM1, alyteserin‐1c, hymenochirin‐2B, and hymenochirin‐4B for pathogenic bacteria were threefold to ninefold lower than the values for the tested probiotic strains. Similarly, temporin‐1DRa and its [Lys 4 ], [Lys 5 ], and [Aib 8 ] analogues showed fivefold to 6.5‐fold greater potency against the pathogens. In the case of PGLa‐AM1, XT‐7, temporin‐1DRa and its [D‐Lys 8 ] and [Aib 13 ] analogues, no apoptosis or necrosis was detected in human peripheral blood mononuclear cells at concentrations below or above the MIC. Given the differential activity against commensal bacteria and pathogens, some of these peptides are promising candidates for further development into therapeutics for topical treatment of skin infections. Abstract : With the aim of identifying antimicrobial peptides that could be further investigated as topical treatments for human or animal skin infections, we determined the MIC values of 14 naturally occurring amphibian peptides and 12 analogues of temporin‐1DRa against clinically relevant pathogens as well as probiotic lactobacilli. Results showed several promising peptide candidates for topical treatment of human or animal skin infections, given the differential activity against commensal bacteria and pathogens.